Do Large Governments Decrease Happiness? - Tiago Neves Sequeira; Tiago Minas; Ferreira-Lopes, A. (46th Annual Conference Money, Macro, and Finance, 2014)
Until now there was little evidence of the influence of large governments on happiness and when it existed, it was positive. We show that structural government consumption and other measures of long-term government imbalances significantly decrease happiness and life satisfaction in European countries. In some cases there is evidence of an inverted U-shaped relationship between the Government burden and happiness, for which the negative relationship begin just before the median. This evidence may lead European politicians to reject the idea that bigger Governments lead to higher people satisfaction and to win elections. This result is consistent with people valuing (negatively) expectations for future tax increases, macroeconomic imbalances, and austerity.